Note to Contributors - Note to contributors (Crossings, 2021)
CROSSINGS: A Journal of English Studies Department of English and Humanities University of Liberal Arts Bangladesh (ULAB) crossings@ulab.edu.bd Volume 12 | September 2021 | ISSN 2071–1107